Sacroperineal mobilization versus posterior sagittal anorectoplasty: A study on outcome - Sivakumar K (Wolters Kluwer Medknow Publications, 2006)
The two main surgical procedures for high and intermediate anorectal malformations (ARM), namely, Stephens′ and Peρa′s procedure, are compared in terms of their outcome. Materials and Methods: Fifty-eight patients who had Stephens′ procedure and 28 patients who had posterior sagittal anorectoplasty (PSARP) are clinically analyzed in terms of associated anomalies, procedural complications, anatomical reconstruction and functional results. Functional results were assessed by Kelly score, voluntary bowel movements and sensation. Statistical analysis of data was done by Chi-square test. Results: There were 34 high and 52 intermediate ARM. Associated anomalies were noted in 32%. Procedure-related complications of urethral injury, bladder injury, neurogenic bladder, anal stenosis and mucosal prolapse were seen in both procedures. Ectopic positioning of anus was seen in 25% of PSARP and 19% of sacroperineal mobilization (SPM). Good circular sphincter creation was seen in 43% of PSARP and 40% of Stephens′. Noncontractile sphincter was found more with SPM. In functional results, when assessed by Kelly score, VBM and sensation, there was no difference for high ARM, whereas results were better with SPM for intermediate anomalies. Discussion: A few reports are available in literature comparing PSARP and SPM. Procedural complications of urethral injury and neurogenic bladder are slightly more with PSARP. Ectopic positioning, poor contraction of sphincter are associated with poor results, and creation of good circular sphincter with good squeeze is associated with good results. Functional assessment by Kelly score, VBM and sensation doesn′t reveal any difference between two procedures for high ARM, whereas for intermediate anomalies, Stephens′ procedure seems to give better functional results.